Synergistic effect of LiF coating and carbon fiber electrode on enhanced electrochemical performance of Li2MnSiO4. (20th March 2021) - Kumar, S. Krishna; Ghosh, Sourav; Bhar, Madhushri; Kavala, Ajay K.; Patchaiyappan, Sivaraman; Martha, Surendra K.
Abstract: Li2 MnSiO4 is a safe, abundant, low cost, and high specific capacity cathode (333 mAh g − 1 ) material for lithium-ion batteries (LIB). This manuscript reports the appreciable improvement in the electrochemical performance of Li2 MnSiO4 by LiF coating by the solid-state method and 3D-electrode architecture. LiF coating on to Li2 MnSiO4 improves interfacial and structural stability thereby enhances the electrochemical performance in terms of initial capacity, capacity retention, and stable cycle life. LiF coating on Li2 MnSiO4 shows a 20% improvement in initial capacity than pristine Li2 MnSiO4 and a stable capacity of 160 mAh g − 1 at 1C rate while pristine Li2 MnSiO4 shows only 60 mAh g − 1 . Fabrication of 3D-electrode by coating Li2 MnSiO4 -LiF composite further improves conductivity thereby enhances the rate capability of the pristine sample. Further, the XPS peak of manganese in Li2 MnSiO4 -LiF suggests that there is a partial replacement of oxygen with fluorine thus enhancing the stability of the crystal system .